Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand - Liu, Dong; Zhang, Zhi-Qiang (Zootaxa, 2019)
A new species of ptyctimous mites of the genus Hoplophthiracarus (Oribatida, Phthiracaridae) is described from the litter of Mercury Islands, Middle Island in the North Island of New Zealand. Hoplophthiracarus sidorchukae sp. nov. differs from its congeners by having 16 pairs of rough and stout notogastral setae, finely punctate body surface, prodorsum without median crista and posterior furrows, interlamellar setae less than three times longer than lamellar setae, and setae h of mentum vestigial. A key to all known species of Hoplophthiracarus in New Zealand is provided.